Policy Implementation of Marine Protected Areas Program in Indonesia: a Case Study of The Marine Recreational Park of Gili Meno, Gili Ayer, and Gili Trawangan, West Nusa Tenggara, Indonesia - A. Boby Yefry Adi Rianto; Bambang Supriyono; M.R. Khairul Muluk (Indonesian Journal of Environment and Sustainable Development, 2014)
Abstract This paper examines TWP Gili Matra as a case study to illustrate the current situation of MPAs in Indonesia. It will use qualitative approach to discuss the extant government policies through key informant interviews and reviews of documents with the consideration of different factors that impede such program which was then analyzed using the policy implementation analysis framework developed by Najam (1995). The result of the study shows that implementation of MPAs policy in TWP Gili Matra has not well implemented yet because of some constraining factors explained by the Najam’s framework. Thus, it need several clear action to be considered in suppressing such constraining factors and improving supporting factor of the management and development of TWP Gili Matra.   Keywords: policy implementation, TWP Gili Matra, 5C Protocol, Marine Protected Area